Interagindo com os números complexos : um material potencialmente significativo para acadêmicos de engenharia - Puhl, Cassiano Scott (2021)
This thesis seeks to understand the impact of the use of the MatEletric multimodal learning object used in the teaching of alternating current electrical circuits to Engineering students, based on the theoretical assumptions of the Meaningful Learning Theory and Problem Solving. This research has a qualitative approach, of the case study type, whose corpus was analyzed from the methodological perspective of Textual Discourse Analysis. The thesis defended is that learning objects can collaborate significantly in the process of content teaching, if the didactic material developed follows the orientations of the assumptions of the Meaningful Learning Theory integrated with the problem solving strategy. In the search for these understandings, a study was conducted in a Higher Education Institution in Serra Gaúcha, in which MatEletric was used by a class of Engineering students who were studying the content of alternating current electrical circuits. MatEletric was used by the professor as a didactic material to introduce general concepts of alternating current electrical circuits, but also to study contents considered basic, enabling a solid knowledge base for the students to learn significantly. Given this context, different instruments were used to build the data of this research: slides that the academics evaluated MatEletric; a virtual questionnaire and semistructured interviews of the academics and the teacher; and the records of the observations of the virtual classes. Within the results obtained, it was found that in the elaboration of multimodal learning objects, as didactic material, in an introductory phase, it is pertinent to contextualize the content, showing its application in real situations, relating it to the professional training of the students, thus seeking to motivate them to make a cognitive effort to construct meaning. The construction of meaning implies considering previous knowledge in the teaching process, because learning occurs when non-arbitrary and non-literal relationships are established between the content studied and the students' knowledge. Therefore, in the elaboration of multimodal learning objects, as didactic material, it should have prior organizers for the students to verify their level of understanding of the knowledge considered as a basis for understanding the didactic content, besides having different didactic resources to fill learning gaps and activate this knowledge in their cognitive structure. Finally, problem solving is a teaching strategy to unify the previous steps - contextualization of content and previous organizers - allowing students to establish new relationships and understand more specific concepts of the content studied. Therefore, it has the understanding that the tripod of the Meaningful Learning Theory, Problem Solving and Digital Technologies are theoretical assumptions with potential to promote the role of the Engineering students in the learning process, overcoming a transmissive and repetitive teaching, through different resources that provide the construction of meanings, the development of skills and abilities considered essential in their professional and personal training.